Lues maligna in a patient with unknown HIV infection - Pföhler, Claudia (BMJ Publishing Group, 2011)
Lues maligna represents a rare form secondary syphilis and is also known as ‘malignant syphilis’ or ‘ulceronodular syphilis’. This clinical entity is predominantly found in immunodeficient patients such as patients with HIV or AIDS. The patient presented here suffered from unspecific symptoms such as painful joints, headache, flu-like symptoms and a disseminated exanthema presenting with ulcerating nodules for 1 week. He further reported a 7 weeks history of painless ulcer, involving his external genitals and anus. Unsafe sexual contacts were strictly denied first, but as serological investigation could prove active syphilis and HIV infection, the patient finally stated promiscuous unprotected homosexual contacts in the past. He was treated with penicillin G intravenously three times daily. The unspecific flu-like symptoms disappeared quickly within several days, all skin lesions healed, partly with scars after 2 weeks.